Produção e capacidade de fitoextração do girassol (heliantus annus) irrigado com água produzida - Costa, Fabrícia Gratyelli Bezerra (2018)
The present work aimed to analyze the effects of treated water in the sunflower crop production system. For that, an experimental area was set up in a greenhouse, in the Department of Agrarian and Forestry Sciences of the Agrarian Science Center of the Universidade Federal Rural do Semi-Árido. The experiment was assembled in a randomized block design with five treatments and five replicates. The treatments used were T1 - 100% application water (AA) and 0% treated treated water (AP), T2 - 75% AA and 25% AP, T3 - 50% AA and 50% AP, T4 - 25% AA and 75% AP and T5 - 0% AA and 100% AP. In the experimental trial 32L pots filled with gravel (nº. zero) were used covering the soil base and soil from the Rafael Fernandes Experimental Farm in Mossoró, being classified as Typic Rhodustults. All plots were fertilized with a foundation. At 90 days after transplanting, the chemical characteristics of the soil were evaluated, using the subdivided plots scheme, with treatments in the subplots, the sampling depths (0 to 0.10 m, 0.20 to 0.30 m ). The physical-chemical characterization of the water produced and the water supply was carried out monthly by means of the collection of three samples during the experimental period. For the productivity, agronomic characteristics, chemical composition of leaves, translocation factors and bioaccumulation, the effects of treatments were analyzed. Data were submitted to analysis of variance, mean tests and orthogonal contrasts. Among the physicochemical attributes monitored in the soil, only Mg2 + contents increased significantly with dilutions of treated treated water, but should emphasize the relevant content of Na + and Cl-1 in treated treated water, which may limit the use of this water for irrigation due to the risks of soil sodification and crop phytotoxicities, especially if it is applied via a sprinkler irrigation system. The effects of treated water on the soil after sunflower cultivation were favorable in terms of supply and availability of nutrients. In addition pH values higher than 7.50 in the treated water and 8.0 in the soil, minimize the environmental risks of heavy metals. There was no negative effect caused by the produced water treated in the biometric agronomic characteristics of the sunflower. Even the chapter diameter of the sunflower showed a significant increase with the use of treated water dilutions. In order to improve knowledge about the sustainable use of water produced for agricultural purposes, it is recommended to carry out complementary studies on the effects of hydrocarbons, hydrocarbons, phenols and other heavy metals in the soil-plant system